Chi sequence protects against RecBCD degradation of DNA in vivo. - Dabert, P (1992)
RecBCD is a multifunctional enzyme involved in DNA degradation and homologous recombination. It also produces an endonucleolytic cleavage near properly oriented chi sites (5'-GCTGGTGG-3'). Plasmids are not known to be affected by either RecBCD enzyme or the presence of a chi site. We report here that plasmids that replicate by a rolling circle mechanism accumulate large amounts of high molecular weight linear multimers (HMW), either if they contain a chi site or if RecBCD is absent. An in vivo inducible system for rolling circle replication was constructed to study RecBCD and its interactions with chi. Results show that (i) HMW accumulation is chi orientation dependent, and (ii) a succession of chi sites prevents degradation of HMW by RecBCD enzyme. These results demonstrate chi activity in plasmids. The rolling circle mechanism produces a sigma structure during plasmid replication; we propose that the double-stranded DNA tail of this sigma form allows RecBCD entry; the tail is degraded unless it is protected by a chi site. By analogy, a principal role of chi in the survival of lambda red-gam- mutants in wild-type strains may be to protect rolling circle concatemers (in late replication) from degradation by RecBCD.